Oxidative cross-dehydrogenative [2 + 3] annulation of α-amino ketones with α-keto esters: concise synthesis of clausenamide analogues. Issue 7 (6th November 2018) - Bhajammanavar, Vinod; Mallik, Sumitava; Baidya, Mahiuddin
Abstract : A one-pot oxidative cross-dehydrogenative [2 + 3] annulation of α-amino ketones with α-keto esters at room temperature is reported. Abstract : A one-pot oxidative cross-dehydrogenative [2 + 3] annulation of α-amino ketones with α-keto esters at room temperature is reported. The protocol features copper/organo cooperative catalysis and provides densely functionalized pyrrolones in high yields. Subsequent reduction furnished multi-substituted pyrrolidinones which represent the core-structure of the natural product clausenamide, a lead molecule for the treatment of Alzheimer's disease.